Missão na Ibiapaba: Estratégias e táticas na Colônia nos séculos XVII e XVIII - Sousa, Mônica Hellen Mesquita de (2003)
This work is a study about the actions between Indians, missionaries, settlers and Portuguese crown around the Ibiapaba Mission, as well as the importance of this settlement in the process of colonization of the captaincy of Ceará in the 17th and 18th centuries [...]